2011
DOI: 10.1016/j.beth.2010.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Parent Training With High-Risk Immigrant Chinese Families: A Pilot Group Randomized Trial Yielding Practice-Based Evidence

Abstract: We studied the efficacy and implementation outcomes of a culturally responsive parent training (PT) program. Fifty-four Chinese American parents participated in a wait-list controlled group randomized trial (32 immediate treatment, 22 delayed treatment) of a 14-week intervention designed to address the needs of high-risk immigrant families. Parents were eligible for intervention if they were Chinese-speaking immigrants referred from schools, community clinics, or child protective services with concerns about p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
90
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 46 publications
4
90
0
2
Order By: Relevance
“…For instance, there is evidence that immigrant families receiving parent-training interventions may need extra practice sessions to acquire the skills taught due to lack of cultural familiarity with these skills (Lau et al 2011). Relatedly, in a study examining the implementation of a culturally-adapted PCIT protocol for Latino families, researchers found that some of the skills taught during the intervention (i.e., the CDI skills and the time-out procedure in the PDI phase) were negatively perceived by these families.…”
mentioning
confidence: 99%
“…For instance, there is evidence that immigrant families receiving parent-training interventions may need extra practice sessions to acquire the skills taught due to lack of cultural familiarity with these skills (Lau et al 2011). Relatedly, in a study examining the implementation of a culturally-adapted PCIT protocol for Latino families, researchers found that some of the skills taught during the intervention (i.e., the CDI skills and the time-out procedure in the PDI phase) were negatively perceived by these families.…”
mentioning
confidence: 99%
“…Adaptations and abbreviated versions of PCIT and the Incredible Years program showed preliminary positive effects in various populations, including Mexican-American families (44), Chinese families (33,45), AfricanAmerican families (46), children in Head Start (47,48), and children identified in pediatric medical settings (31,32,49). Various forms of the Incredible Years program implemented Children randomly assigned to CLAS had fewer inattention and sluggish cognitive tempo symptoms and improved social and organizational skills, compared with those in the control group.…”
Section: Resultsmentioning
confidence: 91%
“…Twelve RCTs that had been published after the previous reviews had been conducted were also identified. Their topics were family-centered behavioral interventions (31)(32)(33)(34), school-based behavioral interventions (35)(36)(37), and integrated behavioral interventions (23,24,(38)(39)(40). Tables 2 and 3 summarize the reviews and the RCTs, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Assessment-guided treatment guarantees that the parents have reached mastery criteria for child-led play and discipline skills before they graduate, which indicates that they have a high level of proficiency with the skills they need to manage their children's behaviors (Eyberg & Funderburk, 2011). Practicing parenting skills until mastery is reached may be especially important for immigrant families, as some of these practices are less culturally familiar and are therefore more challenging to implement successfully (Lau, Fung, Ho, Liu, & Gudiño, 2011;McCabe et al, 2013).…”
Section: Parent-child Interaction Therapymentioning
confidence: 99%